Pengaruh Daya RF terhadap Kandungan Ge dan Sifat Opto-Elektronik Lapisan Tipis a-SiGe:H - Mursal Mursal; Amiruddin Supu; Ida Usman; Toto Winata; Sukirno Sukirno (Institut Teknologi Bandung, 2005)
The effect of rf power on Ge content (CGe) and opto-electronic properties of a-SiGe:H thin films deposited by PECVD method had been investigated. a-SiGe:H thin films were grown on corning glass 7059 substrate from a gas mixture of SiH4 and GeH4 10% diluted in H2, respectively. The substrate temperature was kept at 275oC and the rf power was varied from 50 - 120 Watt. The results showed that the CGe of a-SiGe:H thin films decreases with increasing in rf power, and therefore the optical bandgap (Eopt) increases. We found that the optimum rf power was 90 Watt, which corresponds to the highest photo-sensitivity of 1.43 x 104.